Rural e‐commerce in China: Spatial dynamics of Taobao Villages development in Zhejiang Province. (22nd September 2021) - Lin, Juan; Li, Han; Lin, Mingshui; Li, Chuhai
Abstract: The fast‐growing e‐commerce has dramatically changed the economic structure of China's rural area. As a unique example, Taobao Villages present a brand‐new model to adopt globalization's penetration to achieve rural–urban integration and rural revitalization for developing countries. This study analyzes the spatial trajectory and dynamics of the Taobao Villages development in Zhejiang Province during 2014–2020. We found that these villages were expanding toward the downtown areas of cities, which led to a new pattern of urban–rural division. By constructing panel regression models, we further found that orthodox location factors such as land cost, transportation, and agglomeration played a dominant role in villages' spatial expansion and growth. Regional factors like industrial foundation and labor were also important. These findings suggest that the Taobao Villages in Zhejiang have been upgraded from isolated workshops in rural areas to small manufacturers' clusters and further incorporated into the global urban economy. To better guide and coordinate the development of Taobao Villages, local governments might need to construct e‐commerce parks to achieve an agglomeration economy and industrial upgrading.